Emergency department use among kidney transplant recipients in the United States. Issue 4 (20th December 2017) - Lovasik, Brendan P.; Zhang, Rebecca; Hockenberry, Jason M.; Schrager, Justin D.; Pastan, Stephen O.; Adams, Andrew B.; Mohan, Sumit; Larsen, Christian P.; Patzer, Rachel E.
Abstract : Patients with end‐stage renal disease use the emergency department (ED) at a 6‐fold higher rate than do other US adults. No national studies have described ED use rates among kidney transplant (KTx) recipients, and the factors associated with higher ED use. We examined a cohort of 132 725 adult KTx recipients in the United States Renal Data System (2005‐2013). Data on ED visits, hospitalization, and outpatient nephrology visits were obtained from Medicare claims databases. Nearly half (46.1%) of KTx recipients had at least one ED visit (1.61 ED visits/patient‐year [PY]), and 39.7% of ED visits resulted in hospitalization in the first year posttransplantation. ED visit rate was high in the first 30 days (5.26 visits/PY) but declined substantially thereafter (1.81 visits/PY in months 1‐3; 1.13 visits/PY in months 3‐12 posttransplantation). ED visit rates were higher in the first 30 days versus rates for dialysis patients but less than half the rate thereafter. Female sex, public insurance, medical comorbidities, longer pretransplantation dialysis vintage, and delayed graft function were associated with higher ED use in the first year post‐KTx. Policies and strategies addressing potentially preventable ED visits should be promoted to help improve patient care and increase efficient use of ED resources. Abstract : Nearly half of kidney transplant recipients in the United States visit the emergency department in the first year after transplant, and while emergency visits are higher in the first 30 days, they are less than half the emergency department visit rate compared to first‐year dialysis patients. See Schold and Locke's editorial onpage 777 .